Legal Liability of the Board of Directors for Errors in Withholding and Reporting of Employee Income Tax - Feriawan Ardiawanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study analyzes the legal liability of the Board of Directors regarding the mismanagement of PPh 21 (Employee Income Tax) by subordinates, amidst the ongoing tension between the doctrine of limited liability under the Law on Limited Liability Companies and the concept of personal liability for corporate officers under Tax Law. Employing a normative legal research method with statutory, conceptual, and case-law approaches, this research examines the juridical qualification of delegated authority through the lens of fiduciary duty and the Business Judgment Rule (BJR). The findings indicate that the delegation of payroll management is a legally valid operational action. Following the Constitutional Court Decision Number 41/PUU-XVIII/2020, the paradigm of the Board of Directors' legal liability has shifted from strict liability to fault-based liability. The Directors are shielded from personal liability provided they can demonstrate the implementation of adequate internal control systems (due care) and the absence of criminal intent (mens rea). Liability for administrative tax sanctions rests upon corporate assets, while criminal liability for tax embezzlement committed by individual employees is personal and cannot be automatically imputed to the Directors.